Nitrogen Fertilization Influences the Quantity, Composition, and Tissue Association of Foliar Phenolics in Strawberries - Ashwini Sushil Narvekar; Nishanth Tharayil (Frontiers in Plant Science, 2021)
Unlike quantitative changes, the compositional changes of plant phenolics and changes in their tissue association as influenced by the nutrient supply are less well understood. We evaluated the quantity, composition, and tissue association of phenolics in leaves of two Fragaria ananassa cultivars in response to different levels of nitrogen (N) fertilization using global metabolomic approaches. Influence of N supply on phenolic content in both cultivars was similar, but the magnitude of this response was compound specific. Ellagitannins, the most abundant class of phenolic oligomers, were less responsive to the applied N treatments, whereas proanthocyanidins, the less abundant class of phenolic oligomers, exhibited higher fold change. Within mono-phenolics, the hydroxycinnamates were more abundant but showed lower fold change than the hydroxybenzoates. Among flavonoids, the hydroxylated flavonols showed higher abundances than the flavones, with a preferential accumulation of dihydroxylated flavonol at lower N levels. Furthermore, glycosylated flavonols were higher than the acylated forms. The extractable fraction of phenolics was more influenced by the N treatment than the fiber-bound fraction. The extensive compositional modification of phenolics and a greater response of non-bound fractions in response to N rates highlight the potential to use precise management of N supply as an effective strategy to enhance the bioactive compounds in crops.